Making our place: exploring land-use tensions in Aotearoa New Zealand - Ruru, Jacinta; Abbott, Mick; Stephenson, Janet (Otago University Press, 2011)
Keywords: colonisation; economic aspects; environment; land tenure; land use; social aspects; treaty negotiations

Why New Zealand’s Indigenous reconciliation process has failed to empower Māori fishers: Distributional, procedural, and recognition-based injustices - Bodwitch, Hekia; Song, Andrew M.; Temby, Owen; Reid, John; Bailey, Megan; Hickey, Gordon M. (World Development, 2022)
How is it that the New Zealand government’s process for re-establishing Indigenous fishing rights has failed to deliver thriving Māori fisheries? This paper examines why, at Te Waihora, a coastal lake, and site of one of the nation’s longest running and best-funded state-Māori co-governance agreements, Māori fishers have been unable to use their rights to support their fishery. As of 2018, the lake’s culturally and ecologically significant eel population was no longer commercially viable, a decline fishers have attributed to rampant dairy industry expansion upstream. Drawing on environmental justice literatures, we deploy a multi-dimensional framework to identify factors shaping possibilities for justice in the wake of rights reconciliation, as experienced by Māori fishers, scientists, and leaders. We engage theories of political economic relations to interpret the implications of these experiences for environmental justice theory and politics. Ethnographic accounts demonstrate that the New Zealand government’s process for re-establishing Māori rights falls short of achieving distributional, procedural, and recognition-based dimensions of environmental justice, and that these effects are interlinked. In particular: (i) downstream fishers are placed to bear disproportionate costs of runoff from upstream land use change; (ii) Māori fishers have little influence over governance decisions that affect land use; and (iii) government claims, including that Māori should, “move beyond grievance mode,” obscure logics for resistance. We suggest that the government’s support for dairy industry expansion represents an attempt to mitigate crises of overaccumulation, characteristic of competitive markets. Unlike those who identify persistent injustice as a logic for turning away from the state, we argue that the recurring nature of these crises, and the role state organizations play in directing responses, indicates a rationale for continued engagement with state governing bodies to advance justice.
Keywords: co-governance; economic aspects; environmental justice; equity; fisheries

Here to stay: Reshaping the regions through mana Māori - Kukutai, Tahu; Simmonds, Naomi Beth; Ryks, John (Massey University Press, 2016)
Situated 65 kilometres south-east of Hamilton, Putāruru (population 3747 in the 2013 Census) is typical of the many farming service towns scattered across rural Aotearoa New Zealand. Bakeries, op shops, a sports bar and a farm equipment supplier occupy the main street. Unlike nearby Tirau, which transformed from a one-stop shop into a vibrant boutique village in the late 1990s, Putāruru township remains largely indistinguishable from other rural centres. There are few clues to the substantial farming-based and water-generated wealth that lies beyond the town.
Keywords: economic aspects; mana whenua; tino rangatiratanga

Chapter 40: Indigenous finance: treaty settlement finance in Aotearoa New Zealand - Bargh, Maria (The handbook of diverse economies, 2020)
"Theorising and illustrating diverse, more-than-capitalist economies, this broad-ranging Handbook presents ways in which it is possible to imagine and enact other ways of being. It gathers together empirical examples of diverse economic practices and experiments from across the world, framed by in-depth discussions of key theoretical concepts. Organised into thematic sections, the Handbook moves from looking at diverse forms of enterprise, to labour, transactions, property, and finance as well as decentred subjectivity and diverse economies methodology. Chapters present a wide diversity of economic practices that make up contemporary economies, many of which are ignored or devalued by mainstream economic theory. Pushing the boundaries of economic thinking to include more than human labour and human/non-human interdependence, it highlights the challenges of enacting ethical economies in the face of dominant ways of thinking and being. Economic geography, political economy and development studies scholars will greatly appreciate the empirical examples of diverse economic practices blended with theory throughout the Handbook. It will also benefit policy-makers and practitioners working within diverse economies, or looking to create more ethical ways of living"– Provided by publisher.
Keywords: colonisation; economic aspects; governance; land loss; land ownership; tiriti o waitangi/treaty of waitangi; treaty settlements

A Tika Transition - Bargh, Maria (A Careful Revolution Towards a Low-emissions Future, 2019)
Climate crisis is upon us. By choice or necessity, New Zealand will transition to a low-emissions future. But can this revolution be careful? Can it be attentive to the disruptions it inevitably creates? Or will carefulness simply delay and dilute the changes that future people require of us? This timely collection brings together eleven authors to explore the politics and practicalities of the low-emissions transition, touching on issues of justice, tikanga, trade-offs, finance, futurism, adaptation, and more.
Keywords: climate change; economic aspects; environmental management

Fostering sustainable tribal economies in a time of climate change - Bargh, Maria; Douglas, Sarsha-Leigh; Te One, Annie (New Zealand geographer, 2014)
In this article, we explore how Māori tribal organisations are responding to calls by other Indigenous peoples to become more sustainable in a time of climate change. From a close examination of tribal Environmental Management Plans, we move to a specific case study in the Bay of Plenty area, Ngāti Kea/Ngāti Tuara. Ultimately, we suggest that many tribal organisations are seeking to respond to climate change and transition to becoming producers of their own food and energy needs, and are often articulating these responses in relation to specific local resources and contexts.
Keywords: climate change; economic aspects; environmental management; iwi; iwi development; sustainable development